Effects of Film Thickness and Coating Techniques on the Photoelectrochemical Behaviour of Hematite Thin Films - Kyesmen, Pannan I.; Nombona, Nolwazi; Diale, Mmantsae (Frontiers in Energy Research, 2021)
In this research, three different sets of hematite (α-Fe2O3) films of various thicknesses were prepared using dip, spin, and combined dip/spin coating methods. α-Fe2O3 films of 450–500, 740–800 and 920–980 ± 30 nm thicknesses were prepared using each of the coating methods, and their photoelectrochemical (PEC) behaviour was investigated. Dip coated films produced the best photoresponse while the films prepared using the spin coating method yielded the least photocurrent values across films of different thicknesses. Maximum photocurrent densities of 34.6, 7.8, and 13.5 μA/cm2 V vs reversible hydrogen electrode (RHE) were obtained for the dip, spin and combined dip/spin coated films with a thickness of 740–800 ± 30 nm respectively. Improved crystallization, low charge transfer resistance at the α-Fe2O3/electrolyte interface, high surface states capacitance and the more negative flat band potential values obtained for dip coated films have been associated with the enhanced photocurrent response recorded for the films. The preferential crystal growth of spin coated films in the (104) plane associated with low electron mobility and the high resistance to charge transfer at the α-Fe2O3/electrolyte interface of the films is largely responsible for their low photoresponse. This study underscores the significance of simultaneously optimizing both coating techniques for film deposition and the film’s thickness in preparing nanostructured α-Fe2O3 films for PEC applications.